(untitled) (Scientific journal of the Fergana State University, 2025)
This article discusses the role of Abu Ali Ibn Sina’s scientific heritage in world civilization, human perfection and the development of society. Ibn Sina’s entry into the world of books in his life was due to his strong knowledge of the secrets of medicine. It is emphasized in Ibn Sina’s works that the science of ethics is actually a science that clearly shows the guidelines that ensure people’s happiness and well-being.